2023
DOI: 10.1038/s41419-023-05856-3
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging in articular cartilage by ZMPSTE24 deficiency leads to osteoarthritis with impaired metabolic signaling and epigenetic regulation

Abstract: Osteoarthritis (OA) is an age-related degenerative disease without disease-modifying therapy. The lack of aging-induced osteoarthritis models makes the discovery of therapeutic drugs more challenging. The deficiency of ZMPSTE24 could induce Hutchinson–Gilford progeria syndrome (HGPS), a genetic disorder of rapid aging. However, the relationship between HGPS and OA remains unclear. Our results found that the expression of Zmpste24 was decreased in the articular cartilage during the aging process. Zmpste24 knock… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“… 33 Destabilization of the nuclear membrane further leads to changes in heterochromatin distribution, the epigenetic state of histones, and susceptibility to DNA damage. 28 , 34 , 35 , 36 Mu et al. 33 confirmed that Zmpste24 can regulate the rigidity and stiffness of the nuclear membrane and senescence of stem cells, together with the cytoskeleton.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 33 Destabilization of the nuclear membrane further leads to changes in heterochromatin distribution, the epigenetic state of histones, and susceptibility to DNA damage. 28 , 34 , 35 , 36 Mu et al. 33 confirmed that Zmpste24 can regulate the rigidity and stiffness of the nuclear membrane and senescence of stem cells, together with the cytoskeleton.…”
Section: Discussionmentioning
confidence: 96%
“…This is contradictory to our results, which show that the most suitable nuclear membrane stiffness required for different pressure types and functional organs varies, and it is necessary to strengthen or soften nuclear membranes in different mechanical environments to avoid the negative effects of excessive loading on cells. A large number of studies have explored the mechanism of cellular senescence caused by the decreased expression of Zmpste24, such as epigenetic regulation, 28 oxidative stress, 37 pytoprotection 38 and inflammation. 39 In our study, we found that mechanical overloading and subsequent downregulation of Zmpste24 will generate excess ROS and overexpression of Zmpste24 effectively scavenges it, which implicates that anti-oxidative stress may be a potential mechanism under Zmpste24 protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation